مخطوط تحلية الذهب في علم القضاء والأدب للقاضي أبي عمران المازوني تحقيق جزء من اللوحة 89 ع إلى اللوحة 98 - البار, يحي; طلاب, لخضر (University of Eloued-جامعة الوادي, 2022)
"يدخل عملنا هذا، في إطار تحقيق جزء من مخطوط تحلية الذهب لأبي عمران موسى المازوني من اللوحة 89 عند قوله: ""الغنم الرجوع بالراعي"" إلى اللوحة 98 عند قوله: ""وأنكروا بالقول""، و يهدف إلى إخراج جزء من تراث الأمة لم يسبق أن رأى النور أو نشر من قبل، فيحاول توثيقه بإخراجه كما أراد المصنف أو أقرب ما يكون إليه. فأتى عملنا هذا حاويا قسمين: قسم دراسة وقسم تحقيق. فأما القسم الدراسي فقد ترجم للإمام أبي عمران موسى بن عيسى المازوني، وكذا لكتاب ""تحلية الذهب في علم القضاء والأدب"". وأما قسم التحقيق فكان فيه كتابة النص التراثي، وهو جزء من المخطوط على قواعد الإملاء الحديثة، مع توثيق ما أمكن توثيقه من أقوال بعزوها إلى قائليها. تلت ذلك نتائج من أهمها منهج القاضي المازوني في طرحه للمسائل مع النقل الأمين بعزو الأقوال إلى أصحابها ومصادرها، وهذا يربي الطالب على الأمانة العلمية، ثم التوصية بولوج هذا الباب من تحقيق كتب النوازل الفقه المالكي، بأن يجعل له نصيب وحظ أوفر في البحث الأكاديمي In the frame of shedding the light on our Islamic heritage, we tried our best to be as near as possible to the original ideas included in the work of the writer Abi Amran Moussa Almazoni , from page 89 to page 98 under the tittle of ;Tahliat Eddaheb; the study comes into two folds: The fist is devoted to the study of the original manuscript and the second to its deep academic investigation. The secon fold included the deep review of a part of the manuscript taking into consideration the modern Arabic spelling and deploying ever possible effort to be as near in meaning of the writer; original work. The last point of the study is followed by mentioning the approach of the Scholer Almazoni in talking of certain issues. honestly reciting the writer; intended meaning as well as mentioning the sources and the great contribution of other writers and academic investigators. As fruit of our humble work we learn a lot of good characters such as rightness and humbolnes towards our Scholer and Imams of the nation. Last but not last in importance, we do urge university students to not be afraid to approach this area of academic study for it great benefits for both Islamic heritage and students themselves
مذكرة ماستر
Keywords: النوازل. القضاء. مسائل; cataracts. eliminate. Issues